PENGARUH PRICE FAIRNESS FACILITY DAN SERVICE QUALITY TERHADAP KEPUASAN JAMAAH UMROH PT. RETALI MUSTAJAB TRAVEL MEDAN - Zhubda R, Mahira; Harahap, Nur’ain; Hadian, Arief; Wulandari, Sari (Bisnis-Net, 2025)
Pilgrim satisfaction is the level of feeling that arises after comparing the results provided by a service with the expectations received. Price fairness is the perception of the pilgrim where the difference between the prices received is worthy of being compared and considered acceptable by the pilgrim. Facility is everything that is physical equipment and provided by the organizer to support comfort for the pilgrim, service quality is a marketing strategy to be a benchmark for satisfaction for the pilgrim so as to create a pilgrim loyalty. The purpose of this study is to determine and analyze the effect of price fairness, facilities and service quality partially and simultaneously on the satisfaction of Umrah pilgrims of PT Retali Mustajab Travel Medan. The population in this study is the pilgrim of PT Retali Mustajab Travel Medan, with a sample of 66 pilgrims. The data collection technique used in this study is a questionnaire. The analysis technique used in this study is multiple linear regression, classical assumptions, hypothesis testing and coefficient of determination. The results of the study show that price fairness partially influences the satisfaction of the congregation, this can be seen from the t count (2.308)> t table (1.667) with a significance value of 0.024 <0.05. Facilities influence the satisfaction of the congregation, this can be seen from the t count (1.697)> t table (1.667) with a significance value of 0.111 <0.05. Service quality influences the satisfaction of the congregation, this can be seen from the t count (4.460)> t table (1.667) with a significance value of 0.000 <0.05. Price fairness, facilities and service quality simultaneously influence the satisfaction of the Umrah congregation of PT Retali Mustajab Travel Medan, this can be seen from the F count (9.073)> F table (2.520) with a significance level of 0.000.